Hepatobiliary scintigraphy and its clinical implications: mini review - Afzal, Muniba; Ali, Syed Muhammad; Khairy, Ahmed Talaat; Khattabi, Mazin; Shahid, Fakhar; Ramzee, Ahmed Faidh; Ahmed, Khalid (International Surgery Journal, 2021)
The advent of modern investigations like ultrasound and Magnetic Resonance Imaging has completely revolutionized the diagnosis of gallstones and biliary diseases. However, role of biliary scintigraphy has remained pivotal in some of the biliary tract pathologies especially in detecting the functional problems, leaks and bile reflux. HIDA (hepatobiliary iminodiacetic acid) scintigraphy is conventionally used to diagnose these pathologies and not associated with many harmful effects, although it is time consuming. We reviewed this investigation and its utility in detail encompassing the recent evidence and efficacy.